What attracts people to a career in oral and maxillofacial surgery? A questionnaire survey. Issue 1 (January 2017) - Kent, S.; Herbert, C.; Magennis, P.; Cleland, J.
Abstract: A key aspect of recruiting and retaining the best trainees is identification of the factors that attracted them to OMFS. Although such factors have been examined for medicine in general, we know of no previous study that has looked at those that are specific to OMFS. We distributed a survey online to roughly 1500 people who had registered an interest in OMFS over the past seven years. Personal data, and those about education and employment, were recorded, together with particular factors that drew them to OMFS. Of the 251 trainees who responded, 177 (71%) were interested in a career in OMFS. Differences among sub-groups related to dual qualification, sex, and relationships. Open comments identified the following attractive factors: variety of work, intellectually interesting work, collegiate atmosphere within OMFS, and making a difference to patients. The personalities of those who continued with OMFS training placed high value on achievement, and were more conscientious. The factors identified suggest that the positioning of OMFS as a complex, challenging, and varied hospital-based surgical specialty is key to attracting trainees, and these will be used in future research so that we can move forward from identifying preferences to assessing the relative value placed on those preferences. The data will be useful in the development of strategies to attract new trainees and retain them in the specialty.